Effects of vr-based interactive interior design on the emotional and mental health of office worker - Xiang, Jialing; Mansor, Noranita; Azmi, Athira (Taylor and Francis, 2024)
From the perspective of the evolution of the concept of health, the purpose of mental health is to achieve better living conditions, higher adaptability and development level, and also the best combination of physical and mental well-being and social well-being. According to the literature, the region and privacy of office interior design, the comfort and convenience of office furniture, the charm of office environment and individuation all have an impact on the mental health of office workers. Interactive interior design based on virtual reality can improve the office environment, thus improving the work efficiency and productivity of employees. A comfortable office environment has a positive impact on physical factors for office workers, which is beneficial for improving their mental health. This paper aimed to study how to analyze and study the impact of interactive interior design based on virtual reality (VR) on the emotional and psychological health of office workers. In this paper, the impact of VR interior design was evaluated by fuzzy comprehensive evaluation method, and the analytic hierarchy process (AHP) was used to quantify the weight. In the experiment part of this paper, through the analysis of the questionnaire of the office workers in Chengdu, Sichuan Province, and the comparison of the experimental data, it can be known that before the experiment, the control group and the experimental group were both very healthy, and after the experiment, the psychological health of the two groups was very healthy, which was 0 and 4 people. It can be seen that the psychological health of the workers in the experimental group has changed significantly. This paper studied the influence of VR interaction design on worker’s emotion from the experimental point of view and proved its influence on employee’s emotion from the empirical point of view, which had certain reference significance for future research. © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group on behalf of the Architectural Institute of Japan, Architectural Institute of Korea and Architectural Society of China.